Analisis Penghapusan Merek Terdaftar oleh Direktorat Merek (Studi Pada Direktorat Jenderal Hak Kekayaan Intelektual Kementrian Hukum dan Hak Asasi Manusia Republik Indonesia) - Erlina B (Law Faculty of Universitas Bandar Lampung, 2013)
Request a brand has fulfilled the terms of the formalities in accordance with the provisions of Act No. 15 Year 2001 on the brand, and there is no objection from any party, the Directorate General of Intellectual Property Rights will hold a registration and an official announcement about the companys brand. The results obtained showed that the cause of the abolition of the registered trademark by the Directorate General of Intellectual Property Rights of the Ministry of Justice and Human Rights is a brand not used for three (3) consecutive years in the trade of goods and / or services from the date of registration or the last use. Legal remedies against the removal of a registered mark is the elimination of a lawsuit filed with the Commercial Court, the Decision of the Commercial Court in the case of deletion of a registered mark may be filed Cassation.